Seven-action approaches for the management of hypertension in Asia – The HOPE Asia network - Kario, Kazuomi; Chia, Yook Chin *; Siddique, Saulat; Turana, Yuda; Li, Yan; Chen, Chen Huan; Nailes, Jennifer; Huynh, Minh Van; Buranakitjaroen, Peera; Cheng, Hao Min; Fujiwara, Takeshi; Hoshide, Satoshi; et al. (Wiley, 2022)
Asia is a large continent and there is significant diversity between countries and regions. Over the last 30 years, absolute blood pressure (BP) levels in Asia have increased to a greater extent than those in other regions. In diverse Asia‐Pacific populations, for choosing an Asia‐specific approach to hypertension management is important to prevent target organ damage and cardiovascular diseases. In this consensus document of HOPE Asia Network, we introduce seven action approaches for management of hypertension in Asia.